2022
DOI: 10.1073/pnas.2116182119
|View full text |Cite
|
Sign up to set email alerts
|

Baboon perspectives on the ecology and behavior of early human ancestors

Abstract: For more than 70 y researchers have looked to baboons (monkeys of the genus Papio ) as a source of hypotheses about the ecology and behavior of early hominins (early human ancestors and their close relatives). This approach has undergone a resurgence in the last decade as a result of rapidly increasing knowledge from experimental and field studies of baboons and from archeological and paleontological studies of hominins. The result is a rich array of analogies, scenarios, and other stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Baboons and relatives represent an interesting model for understanding the evolution of behavioural and reproductive plasticity of early humans (J. Fischer et al, 2019; King, 2022). Although most great apes are nonseasonal breeders (Brockman & van Schaik, 2005b; Campos et al, 2017), suggesting that their common ancestor also bred year-round, humans are distinct from other apes by exhibiting much faster reproductive paces (which are similar to most Africa-dwelling papionins: Swedell, 2011), and by living in a wider variety of environments, rather than being restricted to tropical forests (Wells & Stock, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baboons and relatives represent an interesting model for understanding the evolution of behavioural and reproductive plasticity of early humans (J. Fischer et al, 2019; King, 2022). Although most great apes are nonseasonal breeders (Brockman & van Schaik, 2005b; Campos et al, 2017), suggesting that their common ancestor also bred year-round, humans are distinct from other apes by exhibiting much faster reproductive paces (which are similar to most Africa-dwelling papionins: Swedell, 2011), and by living in a wider variety of environments, rather than being restricted to tropical forests (Wells & Stock, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Baboons and relatives represent an interesting model for understanding the evolution of behavioural and reproductive plasticity of early humans (J. Fischer et al, 2019;King, 2022).…”
Section: The Evolution Of Reproductive Flexibility In Anthropoid Prim...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to hominins, baboons evolved in savannah habitats in Africa [ 5 , 6 ], and isotope studies have shown that baboons and early hominins, such as Australopithecus africanus and Paranthropus robustus , exploited similar dietary resources [ 7 ]. A recent review article emphasized the relevance of baboons for human evolutionary studies, as baboons and early hominids are thought to share similarities in environmental flexibility, body size, subsistence strategies, predator avoidance, and the size and structure of their societies [ 8 ].…”
Section: Introductionmentioning
confidence: 99%